Intramolecularly double-donor-stabilized stannylene and its coordination towards Ag(I) and Au(I) centers - Chibde, Purva; Raut, Ravindra K.; Kumar, Vikas; Deb, Rahul; Gonnade, Rajesh; Majumdar, Moumita (Chemistry-An Asian Journal, 2021)
The intramolecularly double-donor-stabilized stannylene 1 has been synthesized from the salt-metathesis reaction between two equivalents of lithium pyridine ene-amide L1 and SnCl2. Compound 1 exhibits dipolar behavior when reacted with B(C6F5)(3) leading to the zwitterionic compound 2. The reaction of 1 with one equivalent and 0.5 equivalent of AgOTf (OTf=trifluoromethane sulfonate) result in the formation of a stannylene-AgOTf complex 3 and a homoleptic distannylene-silver ionic complex 4, respectively. Analogous to complex 4, the gold(I) complex 5 has been synthesized from the reaction between two equivalents of 1 and 0.5 equivalent of AuCl.SMe2/Me3SiOTf. Complex 5 is the first example of homoleptic stannylene-Au(I) ionic complex among the very scarce reports on stannylene-gold(I) coordination complexes. All compounds have been structurally characterized using single crystal X-ray crystallography. Solution-state characterization have been performed using multinuclear NMR techniques. Detailed DFT calculations on the optimized geometries 1 o, 3 o-5 o reveal the change in sp- hybridization on the pyramidal Sn(II) center upon metal coordination and their bonding overlaps.
Keywords: coordination; gold cation; hybridization; intramolecular donor; stannylene

Rh-catalyzed asymmetric hydroformylation of olefins using phosphorus ligands - Kumar, Rohit; Sen, Anirban; Chikkali, Samir H. (Journal of chemical sciences, 2023)
Easily accessible BINOL-based monodentate phosphite ligand L1 and hybrid ligand L2 have been synthesized in good yield by following a one-pot, two-step protocol. A single 31P resonance at 146.6 ppm confirmed the formation of L1. Subsequent 1-2D NMR and mass spectrometric analysis authenticated the existence of L1. These ligands afforded excellent activity and regio-selectivity in the Rh-catalyzed AHF of styrenic substrates. L1 showed excellent regioselectivity but did not discriminate between the two enantiomers, while L2 displayed an enantiomeric excess (ee) of up to 20%. In our attempts to understand the reasons for low ee, the coordination behavior of L2 was investigated. The coordination study revealed that L2 coordinates with the Rh as a monodentate ligand, although there are two P-sites. It was found that only the phosphine arm was coordinated to the Rh and the phosphite arm stayed away from the Rh core at the ambient temperature, leading to moderate ee.Graphical abstractOne-step synthesis of a phosphite (L1) and a phosphine-phosphite (L2) ligand and their implication in the asymmetric hydroformylation of olefins with excellent regioselectivity (>95%) and moderate enantioselectivity (up to 20%) is reported.
Keywords: catalysis; coordination; Hydroformylation; Phosphine-phosphite ligand; Phosphite ligand